Two new stilbenoids from aerial parts of Flickingeria fimbriata. Issue 2 (1st February 2019) - Chen, Dan-Na; Wu, Ya-Ping; Chen, Yue-Juan; Liu, Wen-Jian; Wang, Jing-Xian; He, Feng; Jiang, Lin
Abstract: Two new stilbenoids, named 2, 3 -dimethoxyl-7-hydroxyl-1, 4-phenanthrenedione (1 ) and 2-methoxyl-3-methyl-7-hydroxyl-9, 10-dihydro-1, 4-phenanthrenedione (2 ), together with two known stilbenoids including densiflorol B (3 ) and ephemeranthoquinone (4 ), were isolated from aerial parts of Flickingeria fimbriata (Bl.) Hawkes. The structures of two new compounds were elucidated by extensive spectroscopic analysis, including HRESIMS, 1 H and 13 C NMR, DEPT, HMBC, COSY, HMQC, NOESY. All the compounds were obtained from this genus for the first time. In addition, they all exhibited moderate cytotoxic activities against HepG2 cell lines. Abstract :